A training needs assessment of nurses in their delivery of service quality - Sim, Serene Lee Eng. (2008)
A major Hospital group in Singapore embarked on a service quality improvement program. As part of the on-going efforts, a customer survey was conducted and the results identified a delivery gap. The study is done to apply a systematic approach to conduct training needs assessment and analyzing performance problem.